Determination of Clove Extract Anesthetic Dosage in Transportation Activities of Carp (Cyprinus carpio) Supply Chain - Malik, Andi Adam; Sahabuddin, Sahabuddin; Khairuddin, Khairuddin; Adawiah, Rabiah Al (Department of Agro-industrial Technology, University of Brawijaya, 2021)
AbstractThis study aims to obtain the best dose of clove extract anesthetic in the transportation of carp (Cyprinus carpio) from suppliers to consumers in the supply chain of carp. Alive, healthy, and not defective carp from the Fish Seed Center with 3-5 cm size were used as objects in this study. Carp fish bag and 50 x 35 x 30 cm Styrofoam boxes were used as containers which were placed randomly during the delivery of carp. The study was conducted with four treatments of different clove extract levels, treatment A as a control (0 ppm), B (3.3 ppm), C (6.7 ppm), and D (10 ppm), with three replications each. The examination of the anesthetic condition of carp was carried out four times during transportation, at 0, 6, 12, and 24 hours. Analysis of Variance (ANOVA) was conducted to see the impact of the treatments, and then the Tukey test was carried out to see the differences between treatments. The analysis was carried out using SPSS version 21. The results showed that increasing the anesthetic dose of clove extract impacted the health condition and survival rate of the carp seedlings during transportation. The highest survival rate (85%) was achieved at a concentration of 6.7 ppm.Keywords: anesthesia dosage, clove extract, carp, the survival rate Abstrak Penelitian ini bertujuan untuk mendapatkan dosis anestesi ekstrak cengkeh terbaik dalam pengangkutan ikan karper (Cyprinus carpio) dari pemasok ke konsumen dalam rantai pasok ikan karper. Ikan karper yang digunakan sebagai objek dalam penelitian ini adalah ikan karper dari Balai Benih Ikan dengan ukuran 3-5 cm, dalam keadaan hidup, sehat, dan tidak cacat. Kantong ikan karper dan Styrofoam berukuran 50 x 35 x 30 cm digunakan sebagai wadah selama pengiriman ikan karper dan penempatannya dilakukan secara acak. Penelitian dilakukan dengan 4 perlakuan kadar ekstrak cengkeh yang berbeda, yaitu A sebagai kontrol (0 ppm), B (3,3 ppm), C (6,7 ppm), dan D (10 ppm) dengan masing-masing 3 ulangan. Pemeriksaan kondisi anestesi pada ikan karper dilakukan 4 kali selama pengangkutan, yaitu 0, 6, 12, dan 24 jam. Analysis of Variance (ANOVA) dilakukan untuk melihat dampak dari perlakuan kemudian uji Tukey dilakukan untuk melihat perbedaan antar perlakuan. Analisis dilakukan dengan SPSS versi 21. Hasil penelitian menunjukkan bahwa penambahan dosis anestesi ekstrak cengkeh berdampak pada keadaan kesehatan dan sintasan ikan karper saat transportasi. Sintasan tertinggi (85%) dicapai pada konsentrasi 6,7 ppm.Kata kunci: dosis anestesi, ekstrak cengkeh, ikan karper, sintasan